Reliability Requirements in Mobile Agent Systems - Silva, Flávio Morais de Assis; Macêdo, Raimundo José de Araújo (Anais do Workshop de Testes e Tolerância a Falhas (WTF); 2000: Anais do II Workshop de Testes e Tolerância a FalhasDO - 10.5753/wtf.2000.23466, 2000)
A fundamental issue in the development of mobile agent systems is how to provide support for agent applications reliability. For some agent applications areas (such as electronic commerce or workflow) it is fundamental that mobile agent executions are fault tolerant and exhibit transactional semantics or that groups of mobile agents can coordinate their activities with the use of a reliable communication mechanism. This paper discusses reliability requirements in agent systems and introduces mobile process groups as a suitable underlying concept for fulfilling these requirements. Mobile process groups are an extension of the concept of groups in traditional group communication systems that supports mobility of group members.